Bioinformatics and Computational Biology First International Conference, BICoB 2009, New Orleans, LA, USA, April 8-10, 2009, Proceedings - Rajasekaran, Sanguthevar (Lecture Notes in Bioinformatics, 2009)
This book constitutes the refereed proceedings of the First International on Bioinformatics and Computational Biology, BICoB 2007, held in New Orleans, LA, USA, in April 2007. The 30 revised full papers presented together with 10 invited lectures were carefully reviewed and selected from 72 initial submissions. The papers address current research in the area of bioinformatics and computational biology fostering the advancement of computing techniques and their application to life sciences in topics such as genome analysis sequence analysis, phylogenetics, structural bioinformatics, analysis of high-throughput biological data, genetics and population analysis, as well as systems biology.